Analysis of single PEM fuel cell performances based on current density distribution measurement - Ghosh, P. C.; Wuester, T.; Dohle, H.; Kimiaie, N.; Mergel, J.; Stolten, D. (Journal of Fuel Cell Science and Technology, 2006)
A new in situ measurement method of mapping the current density distribution in polymer electrolyte fuel cells (PEFC) is used to analyze the performance of a fuel cell under different operating conditions. The present method is useful in investigating the current density distribution in a single cell as well as a stack, which carries the information about the local reactant activity over the electrode area It was found that the current density close to the gas inlets is strongly influenced by the reactants' relative humidity. The performance close to the gas outlets is greatly influenced by the inlet gas pressures and the stoichiometry factors of the reactant gases, mainly on the cathode side. It was also observed that the performance of the fuel cell drops with the increase in operating temperature if the reactant gases are not sufficiently humidified.
Keywords: current density distribution; fuel cell performance; PEFC